New Region, New Chances: Does Moving Regionally for University Shape Later Job Mobility? - Felix Ehrenfried; Thomas A. Fackler; Valentin Lindlacher; Thomas Fackler; Thomas Fackler (Center for Economic Studies and ifo Institute (CESifo), 2022)
The extensive literature on university graduates' regional mobility highlights the importance of early mobility but is primarily descriptive. We contribute the identification of the effect of mobility upon high-school graduation on subsequent mobility across labour market regions. The data permit a novel identification strategy that uses the distance to university as an instrument. To ensure comparability, we select high-school graduates from only the suburban region of a large German agglomeration in a university graduate survey. We find that early mobility leads to a sizable increase in later labour mobility, which has implications for labour market efficiency and distributional policy concerns.
Keywords: J61; R23; I23; 330; regional mobility; job mobility; distance to university; students; spatial; instrumental variables estimation